Virtual-Augmented Reality and Life-Like Neurosurgical Simulator for Training: First Evaluation of a Hands-On Experience for Residents - Petrone, Salvatore; Cofano, Fabio; Nicolosi, Federico; Spena, Giannantonio; Moschino, Marco; Di Perna, Giuseppe; Lavorato, Andrea; Lanotte, Michele Maria; Garbossa, Diego (Frontiers in Surgery, 2022)
BACKGROUND In the recent years, growing interest in simulation based surgical education has led to various practical alternatives for medical training. More recently courses based on Virtual Reality (VR) and 3D printed models are available. In this paper, a hybrid (virtual and physical) neurosurgical simulator has been validated, equipped with augmented reality capabilities that can be used repeatedly to increase familiarity and improve technical skills in human brain anatomy and neurosurgical approaches. METHODS The neurosurgical simulator used in this study (UpSurgeOn Box, UpSurgeOn Srl, Assago, Milan) combines a virtual component and a physical component with an intermediate step to provide a hybrid solution. A first reported and evaluated practical experience on the anatomical 3D-printed model has been conducted with a total number of 30 Residents in Neurosurgery. The residents had the possibility to choose a specific approach, focus on the correct patient positioning and go over the chosen approach step-by-step interacting with the model through augmented-reality (AR) application. After that, each practical surgical step on the 3D model were timed and qualitatively evaluated by 3 senior neurosurgeons. Quality and usability-grade surveys were filled out by participants. RESULTS More than 89% of the residents assessed that the App and the AR simulator were very helpful in improving orientation skills during neurosurgical approaches. Indeed, 89.3% of participants found brain and skull anatomy highly realistic during their tasks. Moreover, workshop exercises were considered useful in increasing competency and technical skills required in operating room by 85.8% and 84.7% of residents, respectively. Data collected confirmed that the anatomical model and its application were intuitive, well integrated and easy to use. CONCLUSION The hybrid augmented reality and 3D-printed neurosurgical simulator is a valid tool for neurosurgical training capable of enhancing personal technical skills and competence. In addition, it is easy to imagine how patient safety would increase and healthcare costs would be reduced, even if more studies are needed to investigate these aspects. The integration of simulators for training in neurosurgery as preparatory steps for the operating room should be recommended and furtherly investigated given their huge potential.